Role of Graphene Oxide Aerogel Support on the CuZnO Catalytic Activity: Enhancing Methanol Selectivity in the Hydrogenation Reaction of CO2. Issue 18 (1st September 2022) - Kubovics, Márta; Trigo, Albert; Sánchez, Antoni; Marbán, Gregorio; Borrás, Alejandro; Moral‐Vico, Javier; López‐Periago, Ana M.; Domingo, Concepción
Abstract: A novel CuZnO multicomponent catalyst, involving reduced graphene oxide (rGO) as a support, was synthesized to be applied in the catalytic hydrogenation of CO2 to methanol. The CuZnO@rGO composite was prepared as a 3D aerogel by a two‐step process involving supercritical CO2 for macrostructuration and H2 treatment for reduction. Electron microscopy was applied to visualize the meso/macroporous morphology formed by the supercritical drying. The elemental mapping depicted a homogenous distribution of CuZnO nanoparticles deposited on the rGO flakes. It was demonstrated that methanol production increases for the CuZnO@rGO composite in comparison to unsupported similar CuZnO nanoparticles. This behavior was ascribed to a different interaction established between the Cu 0 and ZnO nanoparticles used as synthetized or deposited on rGO. It is shown that the highly reduced rGO component stimulates H2 O desorption produced during the hydrogenation reaction, thus it serves as a support hindering the sintering of Cu 0 nanoparticles. The formation of a diluted surface alloy of Zn into Cu 0 was determined for the unsupported CuZnO NPs, while for the CuZnO@rGO aerogel composite, the absence of any additional phase, e. g., a surface alloy or reduced ZnO, was confirmed. The composite aerogels show excellent MeOH selectivity at high temperature (up to 260 °C) and low pressure (10 bar). Abstract : CO2 hydrogenation : A novel graphene‐oxide aerogel supported CuZnO catalyst was synthesized for the selective CO2 hydrogenation to methanol. The graphene‐oxide support played a crucial role in the immobilization of the active nanoparticles, as well as in hindering the formation of diluted Cu−Zn surface alloy, which resulted in superior activity and methanol selectivity in comparison to unsupported CuZnO catalyst.